2019
DOI: 10.1111/zph.12661
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of serum antibodies to Coxiella burnetii in Alaska Native Persons from the Pribilof Islands

Abstract: Background Q fever is a febrile illness caused by infection with the bacterium Coxiella burnetii. It is most often transmitted by inhalation of the bacteria after it is shed by infected livestock. Recent studies have found very high C. burnetii infection rates among marine mammals, but it is not known if shedding by marine mammals creates a risk of Q fever among humans. To better understand infection of humans with exposure to marine mammals, the prevalence of antibodies against C. burnetii in serum samples ta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 15 publications
(17 reference statements)
1
3
0
Order By: Relevance
“…By testing plasma samples obtained from individuals living in Southern Netherlands, Brandwagt et al [53] reported significant dynamics in Q fever seroprevalence levels, ranging from 62.5%, as detected in 1983 to 14.4% in 1987, and decreasing to 1% in 2008 and 2.3% in 2010, respectively. Similar data are reported also by other authors [54][55][56][57]. All this clearly showed that there is a lower seropositivity for C. burnetii infection in the general population compared to the risk groups.…”
Section: Discussionsupporting
confidence: 90%
“…By testing plasma samples obtained from individuals living in Southern Netherlands, Brandwagt et al [53] reported significant dynamics in Q fever seroprevalence levels, ranging from 62.5%, as detected in 1983 to 14.4% in 1987, and decreasing to 1% in 2008 and 2.3% in 2010, respectively. Similar data are reported also by other authors [54][55][56][57]. All this clearly showed that there is a lower seropositivity for C. burnetii infection in the general population compared to the risk groups.…”
Section: Discussionsupporting
confidence: 90%
“…The disease caused late-term abortion in ruminants, especially in sheep and goats [ 4 ]. This infection is often asymptomatic in human with a large polymorphism, but several symptoms can be observed at the acute form [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…( 6 ) The Coxiella burnetii bacterium is responsible for Q fever rarely transmitted to humans by pet tricks. It is commonly mild with signs such as the flu, but it can be a serious illness in people with heart valve complications or a failing immune system ( 27 , 28 ).…”
Section: Resultsmentioning
confidence: 99%